Temporal Pattern of Sea Levels in Malaysia - Mohamad Hamzah, Firdaus; Amirah Abdul Ghani, Nur; Abdul Karim, Othman; Nizam Abdul Maulud, Khairul; Mastura Syed Abdullah, Sharifah; Juahir, Hafizan; Ekhwan Toriman, Mohd. (International Journal of Engineering and Technology, 2019)
Sea level rise would be expected to have several impacts, particularly on Malaysia coastal systems such as changes in sedimentation, erosion, flooding and groundwater inundation, storm surge and waves, and sea water intrusion. The purpose of this study is to analyzes the trend variation of sea level rise (SLR) and modelling the SLR for selected locations in Peninsular Malaysia. To examines the trend of the SLR, the curve estimation method, non – parametric Mann – Kendall test and Theil-Sen Trend Line test were used. Then, SLR is modelled in each tidal station. From the analysis, the results showed that all the selected stations in Peninsular Malaysia; Port Klang for hig h tide – no significant trend and for low tide – downward trend, Bagan Datuk for high tide – upward trend and for low tide – no significant trend and Permatang Sedepa for high tide – upward trend and for low tide – no significant trend. This study is important especially for civil engineers, to provide possible solutions to mitigate or eliminate the effects from sea level fluctuations.